2021
DOI: 10.29271/jcpsp.2021.09.1030
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between PI-RADS Categories and Incidental Findings in Multiparametric Prostate MRI

Abstract: Objective: To find the frequency and significance of extraprostatic incidental findings (ep-IFs) during multiparametric-magnetic prostate resonance imaging (mp-MRI), and compare them with prostate imaging reporting and data system (PI-RADS) outcomes. Study Design: Analytical study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In another study, Ediz and Gunduz [ 8 ] detected on secondary reading EPFs in 44 of 185 patients (48%) who underwent multiparametric prostate MRI. They identified inguinal hernias (28% of all patients), bladder wall abnormalities (16%), hydrocele (14%), and sigmoid diverticula (7%) as the most common EPFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, Ediz and Gunduz [ 8 ] detected on secondary reading EPFs in 44 of 185 patients (48%) who underwent multiparametric prostate MRI. They identified inguinal hernias (28% of all patients), bladder wall abnormalities (16%), hydrocele (14%), and sigmoid diverticula (7%) as the most common EPFs.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the previously published literature on the prevalence of EPFs in patients undergoing prostate MRI, we additionally quantified the difference between the frequency of EPFs that were mentioned in the original report (a strategy used by Sherrer et al [ 7 ]) and that were found on secondary targeted reading [ 3 , 8 ]. Heterogeneity in reporting EPFs in primary reports has been recognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, there has been growing attention on MRI of the prostate as new imaging toll, that thanks to the association of DWI and DCE with conventional T1and T2-W imaging, now it is possible to obtain a multiparametric MRI (mpMRI) protocols [28,30,[156][157][158][159][160][161][162][163].…”
Section: Prostate Cancermentioning
confidence: 99%